Ukraine Orthodoxy Autocephaly: Social and Value Challenges - Бродецький, Олександр; Горохолінська, Ірина; Лагодич, Микола (George Fox University, 2020)
The article is devoted to the relevant aspects of the canonical autocephalous status acquisition process for Ukrainian Orthodoxy. The resonant events of the last two years are considered when crucial decisions had been made that led to the emergence of the Orthodox Church of Ukraine as autocephalous on the basis of the Patriarchal and Synodal Tomos granted by the Ecumenical Patriarchate and its acting Primate Patriarch Bartholomew. Sociocultural, geopolitical, and moral aspects of the corresponding processes are conceived. The national and cultural role of the functioning of Ukraine Orthodox Church is considered. The authors analyze the current religious and political situation in Ukraine. The results of actual sociological research dedicated to the religious network and confessional identity of modern citizens of Ukraine, their likes and dislikes as for nationwide religious leaders of Orthodox communities are presented. The research also discusses the state of affairs regarding the recognition of the Orthodox Church of Ukraine by the autocephalous Orthodox Churches of the world. Factors that can intensify or slow down the process of its further recognition are analyzed. A number of topical aspects of the relationship between the Church and the state in the course of the acquisition of autocephaly by Ukrainian Orthodoxy are systematized.
Keywords: Orthodoxy; Autocephaly; Tomos; Orthodox Church of Ukraine; Ecumenical Patriarchate; State and Church relations